Perfectionism among the students of the kindergarten department (Journal of the College of Basic Education, 2023)
The current research aims to identify perfectionism among the students of the Kindergarten Department, and for the purpose of achieving the goal of the research, the researchers used the descriptive approach and the researchers built a scale of perfectionism, and for the purpose of conducting a statistical analysis of the scale of perfectionism, a sample of (300) female students from the Kindergarten Department in the College of Basic Education was selected. - Al-Mustansiriya University and in a random manner from the stages (second - third - fourth), and the researchers extracted the psychometric characteristics of the scale and the use of statistical indicators, and the research reached results, including that the students of the kindergarten department are perfectionists and the results also indicate that there are no statistically significant differences in the perfectionism variable According to the variable of the academic stage of the kindergarten students, and in light of the results of the research, the researcher recommended a set of recommendations and suggestions.